INDUSTRIAL EXPORTS AS A DRIVER OF ECONOMIC GROWTH: AN ANALYSIS OF THE EFFECTIVENESS OF GOVERNMENT SUPPORT MEASURES - Usmonov Murodbek Dusmurot o‘g‘li; Jamilov Firdavs Otabek o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of industrial exports as a driver of economic growth and assesses the effectiveness of government support measures in stimulating export performance and industrial development. Using a combination of theoretical analysis and empirical data, the study evaluates the impact of export-oriented policies on output growth, productivity, and structural transformation.